Usual prevention in unusual settings: A scoping review of place-based health interventions in public-facing businesses. - Jack Tsai; Nicholas A McCann (PLoS ONE)
Place-based health interventions may help reach underserved populations. This scoping review summarizes the peer-reviewed literature on the type and effects of place-based health interventions in unconventional public-facing business settings (e.g., retail and services). A literature search was conducted in PubMed, Google Scholar, and APA PsycNet for studies from 1990-2023. Inclusion criteria for studies were: conducted in the United States, delivered a health intervention, based on an unconventional business setting, and targeted a specific health condition. An initial search yielded 2,727 unduplicated studies, which was filtered to 42 studies included in this review. These 42 studies were categorized based on health conditions of focus, including cardiovascular health (12 studies); HIV (6 studies); diabetes (5 studies); cancers (13 studies); and all other conditions (14 studies). The most common unconventional public-facing business settings for health interventions included barbershops or beauty salons; interventions included health education, preventative screenings, pharmacy services, and connections to local healthcare providers and resources. Notably, 34 (81%) of the studies targeted Black populations. Studies reported positive responses from participants for place-based interventions, increased awareness and screening of health conditions, more referrals to healthcare services, and improved health outcomes. While there have been 9 randomized trials conducted across various health conditions, these trials are limited to focus on a few select settings and lack of objective health outcome measures. These findings highlight the need for more rigorously designed studies in diverse settings that can effectively evaluate the impact of place-based health interventions. The existing literature suggests health interventions delivered in public-facing business settings may be a promising strategy to reach underserved populations.